Survival of microencapsulated probiotic bacteria after processing and during storage: a review - Dianawati Dianawati (Taylor & Francis, 2016)
The use of live probiotic bacteria as food supplement has become popular. Capability of probiotic bacteria to be kept at room temperature becomes necessary for customer’s convenience and manufacturer’s cost reduction. Hence, production of dried form of probiotic bacteria is important. Two common drying methods commonly used for microencapsulation are freeze drying and spray drying. In spite of their benefits, both methods have adverse effects on cell membrane integrity and protein structures resulting in decrease in bacterial viability. Microencapsulation of probiotic bacteria has been a promising technology to ensure bacterial stability during the drying process and to preserve their viability during storage without significantly losing their functional properties such acid tolerance, bile tolerance, surface hydrophobicity, and enzyme activities. Storage at room temperatures instead of freezing or low temperature storage is preferable for minimizing costs of handling, transportation, and storage. Concepts of water activity and glass transition become important in terms of determination of bacterial survival during the storage. The effectiveness of microencapsulation is also affected by microcapsule materials. Carbohydrate- and protein-based microencapsulants and their combination are discussed in terms of their protecting effect on probiotic bacteria during dehydration, during exposure to harsh gastrointestinal transit and small intestine transit and during storage.